2021
DOI: 10.1007/s10461-021-03412-8
|View full text |Cite
|
Sign up to set email alerts
|

The Young Men and Media Study: A Pilot Randomized Controlled Trial of a Community-Informed, Online HIV Prevention Intervention for 14–17-Year-Old Sexual Minority Males

Abstract: The Young Men and Media study developed and pilot tested a community-informed, online HIV prevention program for adolescent sexual minority males (ASMM) in the United States. The developed intervention uses nine interactive modules to increase sexual health knowledge, promote critical examination of pornography, and decrease sexual risk among ASMM. Participants ( N = 154, age 14–17 years) were recruited online in Spring 2020 and randomized to the intervention ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Eight trials combined their online recruitment with offline advertising of the trial [28-29, 33-34, 38-39, 42, 45]. Offline recruitment included advertisements in communities, through healthcare professionals, and schools.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight trials combined their online recruitment with offline advertising of the trial [28-29, 33-34, 38-39, 42, 45]. Offline recruitment included advertisements in communities, through healthcare professionals, and schools.…”
Section: Resultsmentioning
confidence: 99%
“…Only one trial [34] reported how they recruited their PPI group and provided their ages. Two trials [42,44] collected input from clinicians and participants, and Parker, Scull & Morrison [44] further collected feedback from parents. Egan et al [32] interviewed 20 youths from their target population to inform their trial design.…”
Section: Children's Input In the Design Or Conduct Of Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…ASMM ( N = 154, ages 14–17 years) were recruited from March 7, 2020, to May 8, 2020, for a pilot randomized controlled trial of an online sexual health intervention (Nelson et al, 2022). Youth were recruited via online advertising and social media (e.g., Instagram).…”
Section: Methodsmentioning
confidence: 99%
“…Isi intervensi yang diberikan berupa edukasi HIV dan Infeksi Menular Seksual (IMS) yang mana mampu menimbulkan kesadaran secara tidak langsung terkait stres minoritas individu seperti membangun pengetahuan, kesadaran diri, serta efikasi diri. Pendekatan yang efektif dibentuk selama pemberian intervensi sehingga menghasilkan kesadaran diri yang lebih tinggi dalam perilaku pencegahan HIV Nelson et al, (2021). Hasil yang diperoleh tentunya lebih efektif berupa partisipan mampu melakukan tes HIV secara berkala dalam 3 bulan, jumlah seks anal tanpa kondom berkurang, kesehatan seksual meningkat.…”
Section: Pembahasanunclassified